Cutaneous Manifestations, Clinical Characteristics, and Prognosis of Patients with Systemic Sclerosis Sine Scleroderma: Data from the International EUSTAR Database - Lescoat, Alain; Huang, Suiyuan; Carreira, Patricia E.; Siegert, Elise; De Vries-Bouwstra, Jeska; Distler, Jörg; Smith, Vanessa; Del Galdo, Francesco; Anic, Branimir; Damjanov, Nemanja; Rednic, Simona; Ribi, Camillo; et al. (JAMA Dermatology, 2023)
Importance: Systemic sclerosis (SSc) sine scleroderma (ssSSc) is a subset of SSc defined by the absence of skin fibrosis. Little is known about the natural history and skin manifestations among patients with ssSSc. Objective: To characterize the clinical phenotype of patients with ssSSc compared with patients with limited cutaneous SSc (lcSSc) and diffuse cutaneous SSc (dcSSc) within the EUSTAR database. Design, Setting, and Participants: This longitudinal observational cohort study based on the international EUSTAR database included all patients fulfilling the classification criteria for SSc assessed by the modified Rodnan Skin score (mRSS) at inclusion and with at least 1 follow-up visit; ssSSc was defined by the absence of skin fibrosis (mRSS = 0 and no sclerodactyly) at all available visits. Data extraction was performed in November 2020, and data analysis was performed from April 2021 to April 2023. Main Outcomes and Measures: Main outcomes were survival and skin manifestations (onset of skin fibrosis, digital ulcers, telangiectasias, puffy fingers). Results: Among the 4263 patients fulfilling the inclusion criteria, 376 (8.8%) were classified as having ssSSc (mean [SD] age, 55.3 [13.9] years; 345 [91.8%] were female). At last available visit, in comparison with 708 patients with lcSSc and 708 patients with dcSSc with the same disease duration, patients with ssSSc had a lower prevalence of previous or current digital ulcers (28.2% vs 53.1% in lcSSc; P <.001; and 68.3% in dcSSc; P <.001) and puffy fingers (63.8% vs 82.4% in lcSSc; P <.001; and 87.6% in dcSSc; P <.001). By contrast, the prevalence of interstitial lung disease was similar in ssSSc and lcSSc (49.8% and 57.1%; P =.03) but significantly higher in dcSSc (75.0%; P <.001). Skin telangiectasias were associated with diastolic dysfunction in patients with ssSSc (odds ratio, 4.778; 95% CI, 2.060-11.081; P <.001). The only independent factor for the onset of skin fibrosis in ssSSc was the positivity for anti-Scl-70 antibodies (odds ratio, 3.078; 95% CI, 1.227-7.725; P =.02). Survival rate was higher in patients with ssSSc (92.4%) compared with lcSSc (69.4%; P =.06) and dcSSc (55.5%; P <.001) after up to 15 years of follow-up. Conclusions and Relevance: Systemic sclerosis sine scleroderma should not be neglected considering the high prevalence of interstitial lung disease (>40%) and SSc renal crisis (almost 3%). Patients with ssSSc had a higher survival than other subsets. Dermatologists should be aware that cutaneous findings in this subgroup may be associated with internal organ dysfunction. In particular, skin telangiectasias in ssSSc were associated with diastolic heart dysfunction.
CRIS-Team Scopus Importer:2023-10-06